Momentary liquefaction of porous seabed under vertical seismic action. (April 2018) - Chen, Weiyun; Jeng, Dongsheng; Chen, Guoxing; Zhao, Hongyi; He, Rui; Gao, Hongmei
Highlights: The seismic-induced displacements and pore pressure in the seabed are derived analytically. A liquefaction criterion considering the induced excess pore pressure is developed for the seaquake. The potential liquefaction depth in the momentarily liquefied seabed is investigated. The effect of vertical earthquake on liquefaction in seabed should not be neglected. Abstract: The evaluation of potential liquefaction is an important part in the design of marine structures and offshore installations. However, the liquefaction phenomenon of porous seabed under the action of strong earthquake is traditionally been ignored. This paper aims to explore the momentary liquefaction mechanism of porous seabed through the newly analytical solutions of seabed response induced by vertical seismic excitation. Based on the boundary conditions at the surface and bottom of the seabed, the induced displacements and pore pressure in the sediment are rigorously derived as a function of seawater depth, seabed parameters and seismic characteristics of bedrock. A criterion of earthquake liquefaction in the seabed is developed, employing the concept of induced excess pore pressure. The representative cohesionless marine soils with different properties are selected in the parametric analysis. The results show that the liquefaction of seabed could be influenced by seawater parameters, seabed parameters and earthquake ground motion parameters. The significant finding is that current understanding that the vertical motion effect on soil liquefaction is negligible may not always hold true.